A new South American Miocene species of 'one-holed' sand dollar (Echinoidea: Clypeasteroida: Monophorasteridae) - Mooi, Rich; Martínez, Sergio A.; Río, Claudia J. Del (Zootaxa, 2016)
A new species of monophorasterid sand dollar, Monophoraster telfordi n. sp., is described from the Early Miocene basal horizons of the Chenque Formation of Patagonia, Santa Cruz Province, in southern Argentina. The new taxon raises the number of known species in the family to six, and represents first unequivocal record of the genus for the Early Miocene of South America. It is therefore also the oldest member of the genus. M. telfordi is characterized by its test width to length ratio, which is much higher than for the other two described species in the genus, but less than that known for the extremely wide members of the sister taxon, Amplaster. M. telfordi is also unusual among monophorasterids in lacking broad continuity between basicoronal and post-basicoronal plates in the oral interambulacra. A key is provided to all the known species of Monophorasteridae.